Bone Marrow‐Derived Mesenchymal Stromal Cells Harness Purinergenic Signaling to Tolerize Human Th1 Cells In Vivo. (April 2015) - Amarnath, Shoba; Foley, Jason E.; Farthing, Don E.; Gress, Ronald E.; Laurence, Arian; Eckhaus, Michael A.; Métais, Jean‐Yves; Rose, Jeremy J.; Hakim, Frances T.; Felizardo, Tania C.; Cheng, Austin V.; Robey, Pamela G.; et al.
Abstract: The use of bone marrow‐derived mesenchymal stromal cells (BMSC) in the treatment of alloimmune and autoimmune conditions has generated much interest, yet an understanding of the therapeutic mechanism remains elusive. We therefore explored immune modulation by a clinical‐grade BMSC product in a model of human‐into‐mouse xenogeneic graft‐versus‐host disease (x‐GVHD) mediated by human CD4 + Th1 cells. BMSC reversed established, lethal x‐GVHD through marked inhibition of Th1 cell effector function. Gene marking studies indicated BMSC engraftment was limited to the lung; furthermore, there was no increase in regulatory T cells, thereby suggesting a paracrine mechanism of BMSC action. BMSC recipients had increased serum CD73 expressing exosomes that promoted adenosine accumulation ex vivo. Importantly, immune modulation mediated by BMSC was fully abrogated by pharmacologic therapy with an adenosine A2A receptor antagonist. To investigate the potential clinical relevance of these mechanistic findings, patient serum samples collected pre‐ and post‐BMSC treatment were studied for exosome content: CD73 expressing exosomes promoting adenosine accumulation were detected in post‐BMSC samples. In conclusion, BMSC effectively modulate experimental GVHD through a paracrine mechanism that promotes adenosine‐based immune suppression. Stem Cells 2015;33:1200–1212 Stem Cells 2015;33:1200–1212